Technical Skills Required: How Technological Efficacy Influences Online Political Behavior. Issue 3 (2nd July 2016) - Hoffman, Lindsay H.; Schechter, Amanda L.
Abstract : Rapid advances in technology have provided the potential to connect citizens to their surroundings in unprecedented ways. While many scholars examine different types of efficacy as a predictor of behavior (e.g., internal, external, and political), it is essential to examine how confident citizens feel in their ability to use the technology before understanding how they will use it politically. Research shows that perceived competence increases motivation, which is correlated with behavior. This study examined how traditional measures of efficacy and a new measure affect online political behaviors, concluding that technological efficacy is a reliable construct predicting online news use and expression.